Implementasi Fungsi Legislasi DPRD Kabupaten Sidenreng Rappang : PENDEKATAN MODEL GEORGE C. EDWARD III - Suriani.S; Jamaluddin Ahmad; Erfina Erfina (LPPM Universitas Abdurrab, 2026)
This study examines the effectiveness of the legislative function of the Sidenreng Rappang Regency Regional People’s Representative Council (DPRD) using George C. Edward III’s policy implementation framework, which emphasizes four key dimensions: communication, resources, implementers’ disposition, and bureaucratic structure. The research aims to evaluate the extent to which the DPRD’s legislative processes address the needs of an agrarian community characterized by a paternalistic Bugis culture, where reliance on local elites shapes decision-making, while identifying barriers and improvement measures. Employing a qualitative descriptive approach, data were collected through in-depth interviews with three informants (two from the Regional Regulation Drafting Committee and one non-member), analysis of the 2021–2024 Regional Legislative Program (Prolegda) documents, and field observations at the DPRD Secretariat. Thematic coding was conducted using NVivo software to ensure systematic analysis. Findings reveal that legislative performance is suboptimal, with Prolegda realization rates ranging from 50% to 84.6% during 2021–2024. Key obstacles include ineffective communication with the agrarian community, limited budgetary and human resources, low initiative among DPRD members to propose new regional regulation drafts, and fragmented bureaucratic coordination across commissions. Efforts to address these issues, such as socialization via local media and annual training, have been hindered by insufficient funding, infrequent implementation, and lack of specificity in training content. The paternalistic Bugis culture further impedes inclusive community participation, as dependence on local elites limits grassroots input. This study contributes theoretically by enriching policy implementation literature in agrarian contexts and practically by proposing strategies such as increased socialization budgets, specialized legislative training, and village-level forums to enhance public engagement. Limited to a single regency, the findings have constrained generalizability, warranting future research to compare multiple agrarian regions, incorporate quantitative methods, and explore the role of information technology in legislative communication.